LQ control based actuator failure compensation. (28th January 2015) - Wen, L. Y.; Tao, G.; Yang, H.
Summary: In this paper, LQ control based actuator failure compensation schemes are developed for possibly nonminimum phase overactuated systems with actuator failures. The actuator failure is considered as an unmatched input disturbance signal, and a new disturbance rejection problem is formulated as an LQ control problem using a new cost function to enhance output regulation performance in the presence of actuator failures disturbances. Then the failure compensation design is developed to ensure the maximum reduction of the failure disturbance effect on the system output. New controller structures and design conditions are derived through dynamic programming for compensation of actuator failures, including a finite‐time horizon control design and an infinite‐time horizon control design, and their observer‐based counterparts. Closed‐loop stability and output regulation performance are analyzed in details. Simulation results are presented to verify the desired control system performance in the presence of actuator failures, as compared with a traditional design. Moreover, the new LQ based failure compensation schemes are derived in a parametrized framework suitable for adaptive LQ designs to deal with system parameter and failure uncertainties. Copyright © 2015 John Wiley & Sons, Ltd.